2021
DOI: 10.1111/jcmm.16412
|View full text |Cite
|
Sign up to set email alerts
|

Blue LED causes autophagic cell death in human osteosarcoma by increasing ROS generation and dephosphorylating EGFR

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 52 publications
(84 reference statements)
2
11
2
Order By: Relevance
“…When MYC was knocked down or MBTPS2 was overexpressed, the expression of Beclin-1 and LC3 was suppressed, while the P62 expression increased. These findings suggested that autophagy in osteosarcoma cells was inhibited, which was consistent with previous studies [ 34 36 ]. Conclusively, we confirmed the correlation of MYC or MBTPS2 with autophagy and metastasis in osteosarcoma, which provides further verification of the validity of the model.…”
Section: Discussionsupporting
confidence: 93%
“…When MYC was knocked down or MBTPS2 was overexpressed, the expression of Beclin-1 and LC3 was suppressed, while the P62 expression increased. These findings suggested that autophagy in osteosarcoma cells was inhibited, which was consistent with previous studies [ 34 36 ]. Conclusively, we confirmed the correlation of MYC or MBTPS2 with autophagy and metastasis in osteosarcoma, which provides further verification of the validity of the model.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, He et al. (2021) found that blue LED PBMT effectively causes autophagic cell death in human OS cells, which was induced by promoting ROS and the EGFR/Beclin-1-mediated signaling pathway ( 98 ). Recently, Shoorche et al.…”
Section: Phototherapy Of Osteosarcomamentioning
confidence: 99%
“…Blue light, as a visible light with a wavelength range of 400–500 nm, has been clinically applied successfully comprising neonatal jaundice, psoriasis (Pv), atopic dermatitis (AD), eczema, acne, and other inflammatory skin conditions, although the number of available clinical studies evaluating the efficacy of blue light treatment is still limited ( 103 , 136 ). Furthermore, recent studies have demonstrated that blue light irradiation inhibits the proliferation of multiple types of cancer cells in vitro and in vivo , including colon cancer cells ( 14 , 144 , 145 ), malignant glioma cells ( 12 ), melanoma cells ( 10 , 146 , 147 ), B-cell lymphoma cells ( 13 ), fibrosarcoma cells ( 14 ), pancreatic cancer cells ( 15 ), cutaneous squamous cell carcinoma cells (CSCC), epidermoid carcinoma cells ( 148 , 149 ), leukemia cells (Kasumi-1) ( 150 ), bladder cancer cells ( 151 ), colorectal cancer cells ( 152 , 153 ), breast cancer cells ( 91 ), and human OS cells ( 95 , 98 ). Here, we have briefly summarized the relevant research of blue light PBMT in the field of cancer treatment ( Table 1 ).…”
Section: Blue Light Photobiomodulation Therapy In Cancer Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 7 , 8 Furthermore, light irradiation at wavelengths ranging from 450 to 495 nm, which human eyes perceive as blue, has been shown to have antitumor effects on various cancer cells, including melanoma, 9 , 10 lymphoma, 11 colon cancer, 12 , 13 , 14 , 15 leukemia, 16 pancreatic cancer, 17 and osteosarcoma. 18 Therefore, blue light (BL) from LEDs is expected to become a novel non‐invasive therapeutic option in cancer treatment. Although the biological mechanism of BL‐induced antitumor effect is reported to be regulated by cell cycle inhibition, 9 reactive oxygen species, 18 , 19 , 20 , 21 apoptosis, 9 , 12 , 17 , 20 , 22 and autophagy, 11 , 12 , 14 , 18 its role and precise mechanisms remain unclear.…”
Section: Introductionmentioning
confidence: 99%